Epigallocathecingallate (EGCG) Antifungal Properties for Candida Isolates from HIV/AIDS Patients with Oral Candidiasis in Compare with Fluconazole - Dwi Murtiastutik1 , Cita Rosita Sigit Prakoswa2 , Indah Setyawati Tantular3 , Yusuf Wibisono1 , Afif (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Oral Candidiasis (OC) still mainly oportunistic infection problem in HIV/AIDS Patients.Due to increasing report of fluconazole resistant as common antifungal drugs nowadays, there have beenmany studies focusing on natural substances and its antifungal properties. In this study, a form of green teaextract, named Epigallocathechingallate (EGCG) 1,25% were examined for their in vitro antifungal activity against Candida sp in comparison to fluconazole (2 mg/ml) as standard antifungal agents.Objective:To evaluate the antifungal activity of EGCG in compare with fluconazole against Candida isolates takenfrom HIV / AIDS patients with OC. Methods: Fourty Candida sp. isolates taken from HIV / AIDS patientswith OC in the Outpatient Unit and Inpatient Installation of the Infectious Disease Intermediate Care Unit(UPIPI) Dr. Soetomo, Surabaya. Antifungal activity were evaluated by using microdilution tests. Results:The microdilution test revealed the MIC of EGCG for all Candida sp. was 0.625%, while the MIC offluconazole was 100% for all Candida sp. There was significant difference (p <0.05) between the MICvalues for Candida sp. by fluconazole and EGCG. The MFC values of EGCG was 50%, while value offluconazole MFC was 100%. Conclusion: Antifungal activity of EGCG with fungistatic and fungicidaleffect is better than fluconazole.